Augmenter of Liver Regeneration (ALR) Protects Kidney from Ischemia/Reperfusion (I/R) Injury via Regulation of TLR4/MAPK Signaling Pathway - Ying Li; Yanying Xiong; Huihui Li; Yan Luo; Ling Zhang; Qin Zhang; Weijian Xiong; Haitao Tu (Journal of Immunology Research)
Toll-like receptor 4 (TLR4) can mediate innate activation and inflammation, and it is typically expressed within the ischemic kidney. Augmenter of liver regeneration (ALR) acts as an immunoregulator with a high expression in the kidney induced by renal ischemia/reperfusion (I/R) injury. Exogenous ALR has indicated a role in protecting the kidney from I/R injury. The protective effect of ALR is due to the immune regulatory function which remains to be elucidated. In this study, rats induced by renal I/R were treated with recombinant human ALR (rhALR) and demonstrated that the animals were protected from kidney I/R injury, implying that the rhALR-treated rats had less tubular damage than those untreated rats. Meanwhile, tubular epithelial cell apoptosis, neutrophil (24 h) and macrophage (72 h) infiltration to tubulointerstitium, and levels of inflammatory cytokines were decreased considerably in the rhALR-treated rats as compared to control. Additionally, rhALR could downregulate mRNA expression of TLR4 endogenous ligands and restrain its activation in renal I/R injury rats. It has also been proved that anti-rhALR antibody blocked the inhibition of rhALR of the immune inflammatory response in hypoxia/reoxygenation (H/R) injury in vitro. In rhALR+anti-rhALR antibody-intervened H/R cells, the expression of inflammatory cytokines was upregulated compared with the rhALR-treated cells. Taken together, rhALR could regulate the TLR4 signaling pathway to relieve inflammatory response, thereby protecting renal I/R injury, indicating that ALR is likely to be introduced to develop novel immune therapies for renal I/R injury.